Scenario 2: victorian development - Heyden, Lutz Karl Von Der (2022)
In the subsequent Work Project, scenarios were built based on a deductive evaluation of potential supply strategies for green hydrogen. The framework for Dortmund Energy and Water Supply GmbH's (DEW21) future strategic alternatives was established by researching the external environment and conducting interviews with three essential experts. The reader is introduced to a spectrum of potential futures for the hydrogen sector and threats and opportunities that may emerge within the specified time frame. Finally, comprehensive strategy advice is provided to the company.